Chapter 8 Hostile in tent Reconsidering the roles of viking encampment across the Frankish realm - Cooijmans, Christian (Taylor & Francis, 2023)
When considering the establishment of overseas viking encampments, some of the most detailed and vivid contemporary descriptions of this activity originate from the Frankish realm, a region which nevertheless remains precariously positioned in wider comparative investigations of the viking world. To address this imbalance, this chapter assembles and reassesses the extant evidence for these camps across this expansive territory, whilst providing a distinct, continental perspective on their establishment, operational parameters, and overall strategic significance. In doing so, it affirms that these encampments would have represented much more than mere ramparts for vikings to bide their time behind, as they offered opportunities to regroup, recuperate, and perform repairs; to build up rations and other reserves; to conduct reconnaissance; and to engage in commerce and craft production. By and large, they would have been carefully planned and highly organised spaces, whose continued operation would have revolved around the collective, coordinated efforts and expertise of their occupants. All things considered, the available evidence alludes to a highly intricate and dynamic landscape of regional viking encampment, which would have played a principal part in keeping the viking phenomenon afloat and afoot across the Frankish realm.